The Integrity in the product and movement of architecture - Kadhim, Ibrahim Jawad (Iraqi Journal of Architecture and Planning, 2017)
Integrity affects in the development methods of the architectural projects, creativity contexts carrying new characters which increase it is effectiveness. Finding the way of dealing with a designer and recipient of the architectural product. Therefore, the research question in the integrity architectural movement throughout it is history and the compatibility between the product and movement of architecture. The research determined methodology included the answer of the question with two methods in; Analytical approach, and represent ;( 1) agreement method in a change of place. by using design act in how it integrates architecture between it is visible and invisible systems thought architectural product.(2)The difference method in the movement of time, the integration of architectural movement ,by measurement concept of Aristotle through the behavior of designer .and from these methods achieved between the constituent elements of the architectural product to demonstrate the integration and decadence of the production cycle, while the rational approach was used as a special integrative approach. The research found that the loss of boundaries between integration and decadence, and they’re being two degrees of degrees the presence of the integrity architectural product movement.